Islamic ethics and the trusteeship paradigm : Taha Abderrahmane's philosophy in comparative perspectives = al-Akhlāq al-Islāmīyah wa-nasaq al-iʼtimānīyah : muqārabāt fī falsafat Ṭāhā ʻAbd al-Raḥmān - Hashas, Mohammed; Khatib, Mutaz (Studies in Islamic ethics,, 2020)
Islamic Ethics and the Trusteeship Paradigm explores the emerging ethical theory of the trusteeship paradigm as developed by the Moroccan philosopher Taha Abderrahmane (b. 1944). The volume, with contributions in English and Arabic, examines the development of this modern Islamic theory of ethics and how it permeates various disciplines: philosophy, theology, legal theory, moral theory, sociology and anthropology, communication, environment and biomedical ethics. The trusteeship paradigm aims to make ethics the compass of human thinking and action in order to overcome the predicaments humanity faces and realize a more just and balanced world. This makes of it one of the principal and profound ethical theories in Islamic scholarship that engages both classical and modern thought.